FACTORS THAT HINDER COMMUNITY-BASED SECONDARY SCHOOLS IN TANZANIA FROM IMPLEMENTING THE CURRICULUM EFFECTIVELY: A CASE STUDY OF TABORA REGION - Assey, Ernest S.; Malingumu, Winfrida; Babyegeya, Emmanuel (Journal of Education and Practice, 2022)
Purpose: This study focused on factors that hinder community-based secondary schools in Tanzania from implementing the curriculum effectively. Methodology: A case study research design was used in this study. The data were gathered through focus group discussions and interviews with 147 people from various educational cadres, including heads of secondary schools, teachers, District Education Officers (DEO), Quality Assurer's (QA), parents and students. Findings: Poor reading culture among students, poor teaching and learning environments, a problem with the medium of instruction, poor parental engagement in children's education, teacher shortages, poor managerial skills among school leaders, and a lack of in-service training among teachers are the main factors that hinder effective curriculum implementation community-based secondary schools in Tanzania, according to the findings of the study. Unique contribution to practice, theory and strategy: The study's findings help educational stakeholders better understand how curriculum implementation is impacted when a school lacks adequate teaching and learning infrastructure, adequate teaching and learning materials, adequate teaching staffs, and adequate funding to support in-service training for teaching staff. The study's conclusions also supported Rogers' Diffusion Theory's main claim, which holds that effective curriculum implementation is a function of the school environment, which ensures effective interaction between teachers and students as well as teaching and learning materials, as opposed to ineffective curriculum implementation if the school environment does not ensure effective interaction. Recommendations: The study recommended that Tanzania's government should continue with initiatives to increase the number of teachers, revise the policy governing the medium of instruction in schools, improve the teaching and learning environment as well as infrastructures, schools should fully engage parents in decision-making, improve in-service teacher training, and school heads should undergo frequent training on pedagogical leadership skills as a means of ensuring effective curriculum implementation in community-based secondary schools.